On weakly s -normal subgroups of finite groups - Li, Yangming; Qiao, Shouhong (Український математичний журнал, 2011)
Assume that G is a finite group and H is a subgroup of G. We say that H is s-permutably imbedded in G if, for every prime number p that divides |H|, a Sylow p-subgroup of H is also a Sylow p-subgroup of some s-permutable subgroup of G; a subgroup H is s-semipermutable in G if HGp=GpH for any Sylow p-subgroup Gp of G with (p,|H|)=1; a subgroup H is weakly s-normal in G if there are a subnormal subgroup T of G and a subgroup H∗ of H such that G=HT and H⋂T≤H∗, where H∗ is a subgroup of H that is either s-permutably imbedded or s-semipermutable in G. We investigate the influence of weakly s-normal subgroups on the structure of finite groups. Some recent results are generalized and unified. Нехай G — скiнченна група, а H — пiдгрупа G. Будемо говорити, що H є s-переставно вкладеною в G, якщо для будь-якого простого числа p, що дiлить |H|, силовська p-пiдгрупа H є також силовською p-пiдгрупою деякої s-переставної пiдгрупи G; H є s-напiвпереставною в G, якщо HGp=GpH для будь-якої силовської p-пiдгрупи Gp групи G iз (p,|H|)=1; H є слабко s-нормальною в G, якщо iснують субнормальна пiдгрупа T групи G i пiдгрупа H∗ пiдгрупи H такi, що G=HT i H⋂T≤H∗, де H∗ — пiдгрупа H, що є або s-переставно вкладеною, або s-напiвпереставною в G. Дослiджено вплив слабко s-нормальних пiдгруп на будову скiнченних груп. Узагальнено та унiфiковано деякi нещодавнi результати.